The Relationship Between The Implementation of Occupational Safety and Health Management and Work Productivity in The Engine Room of Km. Dharma Kartika IX - Iksan Brahmada; Dirhamsyah; Diyah Purwitasari; Agus Prawoto; Intan Sianturi (International Journal of Science and Environment (IJSE), 2026)
The maritime sector faces rising ship accidents, with 3,310 cases in 2024, highlighting risks in engine rooms. This study aims to analyze the relationship between occupational safety and health management (K3) implementation and work productivity in the engine room of KM. Dharma Kartika IX. Using a quantitative correlational cross-sectional design, data were collected via Likert-scale questionnaires from 30 purposive-sampled engine room workers during 12 months in 2026. Instruments were validated (Pearson, r_table=0.306) and reliable (Cronbach Alpha >0.60), analyzed with simple linear regression via SPSS 26, including prerequisite tests (normality, linearity). Results show a significant positive influence (t=4.305 >1.701, sig=0.001, R=0.780, R²=0.608; Y=22.892+0.253X), with high variable descriptions. In conclusion, enhanced K3 boosts productivity by 60.8%, recommending training and SOP enforcement